The hemicellulose extract from Cynara cardunculus: a source of value-added biomolecules produced by xylanolytic thermozymes. Issue 8 (23rd December 2015) - Finore, Ilaria; Poli, Annarita; Di Donato, Paola; Lama, Licia; Trincone, Antonio; Fagnano, Massimo; Mori, Mauro; Nicolaus, Barbara; Tramice, Annabella
Abstract : The hemicellulose fraction from Cynara cardunculus was efficiently degraded and converted into xylo-conjugates by the thermophilic xylanolytic enzymatic systems of Geobacillus thermantarcticus . Abstract : The Cynara cardunculus hemicellulose fraction was recovered from its stem and leaf biomass and converted into valuable molecules by exploiting the extracellular xylanase and β-xylosidase activities produced by the thermophilic bacterium Geobacillus thermantarcticus . Several degradation procedures for the arabinoglucuronoxylan extract were proposed by using efficient and different enzymatic preparations, containing both or only one xylanolytic activity of G. thermantarcticus . In particular, when the xylanase and β-xylosidase activities were used separately in hydrolysis reactions, xyloglucurono-oligosaccharides or xylose were obtained with a yield of 32% and 62.6% respectively, with reference to the hemicellulosic extract. Furthermore, the synergic action of β-xylosidase/xylanase activities was exploited in transglycosylation processes for the production of xylo-conjugated compounds; xylosides of primary alcohols with increasing carbon chains and aromatic alcohols were produced starting from the C. cardunculus hemicellulose, which was selected as a cheap donor. When 2-phenoxyethanol was selected as an acceptor, 2-phenoxyethyl β-xyloside, xylobioside and xylotrioside were prepared with a yield of 38.5% with respect to the hemicellulosic extract and spectroscopically characterized.